APPLICATION OF GUIDED-NOTE TAKING METHOD WITH HANDOUT IN MATHEMATICS LEARNING FOR GRADE X (TEN) OF SENIOR HIGH SCHOOL STUDENTS IN SMAN 1 HILIRAN GUMANTI SOLOK - Anesia Noviliza (Ensiklopedia of Journal, 2020)
This study aims to see how the application of guided note-taking method with hand out might improve the student’s mathematics learning outcome in SMAN 1 Hiliran Gumanti Solok which are under minimum completeness criteria (KKM). This is due to the limited resources of student learning such as books and the internet because SMAN I Hiliran Gumanti was currently established with limited library book collection and located far away from the internet connection could reach. One way that teachers can do to solve this dilemma and increase the positive learning process for the students is by applying a guided note-taking method accompanied by handout. This research is a quasi-experimental research with a randomized control group only design for its research design. The population for this research is all grade ten students in SMAN I Hiliran Gumanti who are divided into three class namely class X.1, X.2, and X.3. The sampling technique is random sampling after applying the normality and the homogeneity test for the three classes and then randomly select two classes as the sample class by drawing numbers. The drawing selects X.3 as the experimental class and X.1 as the control class. The data obtained from the final test of the two classes are processed and then interpreted. The result shows that the average final test score from the experimental class is higher than the control one, which is 69.7 and 60.5 respectively. The student activities during the learning process also observed and then processed with percentage techniques. The conclusion attained is positive activities during the learning process in the experimental class are increased whereas the negative activities decreased. Lastly, the final test data processing obtained by using a t-test. The result is t-value > t-table (1.794 > 1.654), it shows that the proposed hypothesis is accepted. This means that the application of guided note-taking with handout is successfully rising-up the student’s mathematics score in SMAN I Hiliran Gumanti.